Glass forming ability and crystallization behavior of Ti-based amorphous alloys with high specific strength - Kim, YC; Bae, DH; Kim, WT; Kim, DH (ELSEVIER SCIENCE BV, 2003)
Thermal. stability and crystallization behavior of melt-spun Ti50-xCu25Ni15Sn3Be7Zrx (x = 0, 1, 3, 5 and 7) amorphous alloys have been investigated using differential scanning calorimetry (DSC), X-ray diffractometry and transmission electron microscopy. With increasing Zr content, x, from 0 to 7, both DeltaT(x)(= T-x - T-g) and T-rg (= T-g/T-1) gradually increase from 45 to 56 K and from 0.53 to 0.60, respectively, indicating that the alloys containing Zr have a good glass forming ability, where T-g, T-x, and T-1 are glass transition, crystallization, and liquidus temperatures, respectively. The Ti50Cu25Ni15Sn3Be7 alloy shows three endothermic events in the DSC curve; initially the alloy crystallizes by forming crystalline phase a few nanometers in scale, followed by decomposition into a mixture of Ti(Ni,Cu), TiCu, Ti3Sn, and TiBe12 phases at high temperature. On the other hand, the alloys containing Zr consist of only nanocrystalline phases around 10 nm in size even after the second endothermic event due to their increased atomic packing density. For the Ti45Cu25Ni15Sn3Be7Zr5 alloy, fully amorphous rods up to 5 mm in diameter are successfully fabricated by injection casting. The amorphous alloys exhibit high compressive strength around 2500 MPa with good ductility. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: SUPERCOOLED LIQUID REGION; MECHANICAL-PROPERTIES; METALLIC GLASSES